Investigating impacts of implementing NEW road pricing system - Chong, Ke Chun (Nanyang Technological University, 2022)
In Singapore, about 12% of land is taken up by road network, which supplies the important infrastructure for mobility. Herein, good transport planning and management are critical towards minimising traffic congestion on our road network. Singapore implemented the road pricing system as a key demand management measure since 1974, and the present system, the Electronic Road Pricing (ERP) system, was implemented in 1998. The ERP allows automatic electronic payment deduction as vehicles drive through control gantries, and the ERP is therefore a fixed-point mobility tracking system. There is now well-established technology by way of satellite-based geospatial tracking to provide near continuous mobility tracking system. Herein, the Land Transport Authority (LTA) is now implementing the Global Navigation Satellite System (GNSS), which allows distance-based charging. With GNSS, there shall be an On-Board Unit (OBU) for communications and charging utility.